2015
DOI: 10.1128/jcm.01691-15
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Commercial Molecular Assays for Detection of Rifampin and Isoniazid Resistance among Mycobacterium tuberculosis Isolates in a High-HIV-Prevalence Setting

Abstract: cIn a head-to-head comparison of the MTBDRplus version 2.0 (Hain Lifescience), the Xpert MTB/RIF (Cepheid), and the Anyplex MTB/NTM (Seegene) assays, we demonstrated equal sensitivity (59/61; 96.7%) and specificity (53/54; 98.1%) for detecting rifampin resistance with further analysis of discordances. The Xpert assay does not detect isoniazid resistance while the Anyplex assay showed high false positivity. There are a limited number of commercial molecular assays available for the rapid detection of drug-resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…On one and a half year of follow-up, this particular patient improved clinically without receiving MDR treatment. Similar observation has been made by prior researchers who have documented at least one case of false rifampicin resistance by MTBDRplus assay in comparison with rpoB sequencing, 24 DST, 20,21 or CRS. 18 Such cases of false rifampicin resistance could have arisen due to cross-contamination at any step of the assay thus emphasizing the importance of separate working areas for each step.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…On one and a half year of follow-up, this particular patient improved clinically without receiving MDR treatment. Similar observation has been made by prior researchers who have documented at least one case of false rifampicin resistance by MTBDRplus assay in comparison with rpoB sequencing, 24 DST, 20,21 or CRS. 18 Such cases of false rifampicin resistance could have arisen due to cross-contamination at any step of the assay thus emphasizing the importance of separate working areas for each step.…”
Section: Discussionsupporting
confidence: 87%
“…Further, unlike our study, none of these studies have confirmed their results by carrying out gene sequencing for the offending drug. Two other studies, 15,24 comparing results of MTBDRplus assay version 2.0 with sequencing have reported a sensitivity of 96.7 and 100%, respectively, for detecting rifampicin resistance and 100% each for detecting isoniazid resistance. The present study differs from these two by the fact that while the former was carried out on 115 culture-positive undefined (PTB or EPTB) samples, the latter was conducted on mere eleven VF samples from cases of IOTB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation